THE RESULTS OF AN INVESTIGATION TO PRODUCE A SELF-HELP MANUAL: MANAGE OF STRESS IN FAMILIES WITH A CASE OF GASTRIC CANCER - Espinoza Ortiz, Catalina (2012)
This investigation approaches the subject of stress in families with a case of gastric cancer, gathered information related to the cognitive, behavioral and emotional aspects that must be contained in a manual of self-help, which explains how to face situations of stress in families with the mentioned characteristics. This manual has been created from the analysis of such results, and it consists of written and auditory material, which we hope, prepares families to cope with stress management in order to avoid, as much as possible, that stress becomes a negative influence in the recovery of the patient and the family atmosphere.